Changes in Plant Based Diets and Subsequent Risk of Type 2 Diabetes: Results from 3 Large US Cohorts - Cheng, Zhangling (Curr Dev Nutr, 2020)
OBJECTIVES: Plant-based diets may lower type 2 diabetes (T2D) risk. Whether changes in adherence to plant-based diets are associated with subsequent T2D risk remains unknown. We aimed to evaluate the associations between 4 year changes in plant based diets and subsequent 4 year risk of T2D. METHODS: We prospectively followed 76,530 women in the Nurses’ Health Study (NHS, 1986–2012), 81,586 women in NHS II (1991–2017), and 34,468 men in the Health Professionals’ Follow-up Study (1986–2016). Diet was assessed every 4 years using validated food-frequency questionnaires. Adherence to plant-based diets was assessed using previously developed indices – the overall plant-based diet index (PDI), the healthful PDI (hPDI), and the unhealthful PDI (uPDI). Self reported T2D cases were validated by supplementary questionnaires. We used multivariable time dependent Cox proportional hazards models to estimate hazard ratios (HR) and 95% CIs for T2D associated with 4 year changes in adherence to plant based diets. Results of the three cohorts were pooled using an inverse variance-weighted meta-analysis. RESULTS: We documented 12,016 cases of T2D during 2818,485 person-years of follow-up. After adjustment for initial BMI, initial and 4-year changes in lifestyle and other factors, compared with participants whose indices remained relatively stable (±3%), participants with the largest 4-year decrease (>10%) in PDI and hPDI had a 12%-23% higher T2D risk in the subsequent 4 years (HR for PDI, 1.12 (95% CI 1.05, 1.20), HR for hPDI, 1.23 (1.16, 1.31)). Conversely, each 10% incremental increase in PDI and hPDI over 4 years was associated with a 7%–9% lower T2D risk in subsequent 4 years (HR for PDI, 0.93 (0.90, 0.95), HR for hPDI, 0.91 (0.87, 0.95)). Changes in uPDI were not associated with T2D risk. Further adjustment for concurrent changes in body weight, a potential mediator, modestly attenuated the associations but results remained significant. We estimated that body weight changes explained 6.0%–36% of the associations between 4 year changes in PDI and hPDI and subsequent T2D risk. CONCLUSIONS: Improving adherence to overall and healthful plant based diets over a 4 year period was associated with a lower T2D risk, whereas decreased adherence to overall and healthful plant based diets was associated with a higher T2D risk. FUNDING SOURCES: Nutricia Research Foundation/NIH.